2016
DOI: 10.1186/s13075-016-0920-6
|View full text |Cite
|
Sign up to set email alerts
|

A longitudinal genome-wide association study of anti-tumor necrosis factor response among Japanese patients with rheumatoid arthritis

Abstract: BackgroundStudies of Caucasian patients with rheumatoid arthritis (RA) to identify genetic biomarkers of anti-tumor necrosis factor (TNF) response have used response at a single time point as the phenotype with which single nucleotide polymorphism (SNP) associations have been tested. The findings have been inconsistent across studies. Among Japanese patients, only a few SNPs have been investigated. We report here the first genome-wide association study (GWAS) to identify genetic biomarkers of anti-TNF response… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 59 publications
1
24
1
Order By: Relevance
“…While researchers believe that disease risk variants are responsible for the heterogeneous aetiology of RA, the use of genetic data in the prediction of clinical phenotype is challenging. Previous GWAS examining the response to biologics (mainly anti-TNF therapy) provided unsatisfactory evidence,63–67 which may suggest that genetic background of RA onset and that of clinical response are distinct. A crowd-sourced collaborative assessment of SNP data to predict anti-TNF treatment response was performed 68.…”
Section: What Can We Learn From Genetics Of Ra?mentioning
confidence: 99%
“…While researchers believe that disease risk variants are responsible for the heterogeneous aetiology of RA, the use of genetic data in the prediction of clinical phenotype is challenging. Previous GWAS examining the response to biologics (mainly anti-TNF therapy) provided unsatisfactory evidence,63–67 which may suggest that genetic background of RA onset and that of clinical response are distinct. A crowd-sourced collaborative assessment of SNP data to predict anti-TNF treatment response was performed 68.…”
Section: What Can We Learn From Genetics Of Ra?mentioning
confidence: 99%
“…In addition, that study confirmed the association of 35 known non‐ HLA loci at the genome‐wide level of significance in Koreans. A Japanese GWAS was conducted to identify genetic biomarkers that can predict response to anti‐TNF agents in RA patients that showed three loci within the MAP3K7‐BACH2 , GFRA1 and WDR27 genes are associated with anti‐TNF response in Japanese RA patients . Recently a multinational Arab RA GWAS was undertaken in 794 RA cases and 573 controls that discovered two novel RA risk loci within the CDH6 and SMTNL2/GGT6 gene regions .…”
Section: Genetic Factors That Contribute To Ra Pathogenesismentioning
confidence: 99%
“…89 Eyre et al 58 GWAS was conducted to identify genetic biomarkers that can predict response to anti-TNF agents in RA patients that showed three loci within the MAP3K7-BACH2, GFRA1 and WDR27 genes are associated with anti-TNF response in Japanese RA patients. 95 Recently a multinational Arab RA GWAS was undertaken in 794 RA cases and 573 controls that discovered two novel RA risk loci within the CDH6 and SMTNL2/GGT6 gene regions. 96 RA-associated loci at a genomewide level of significance are shown in Table S1, Supporting…”
Section: Genetic Factors That Contribute To Ra Pathogenesismentioning
confidence: 99%
“…Environmental or clinical factors such as smoking, gender, age, baseline disability, or presence of autoantibodies account for only a small proportion of the variability in patient response [2, 3]. Unfortunately, genome-wide association studies (GWASs) have so far not revealed any clear evidence of predictive genetic markers, except for a large collection of nominally significant markers [48], or a few markers which, despite having approached acceptable levels of significance, are too weak to inform any clinical decisions (such as rs6427528 on CD84 with p  = 8 × 10 –8 in the etanercept subsets of patients) [9]. …”
Section: Introductionmentioning
confidence: 99%